Internalisasi Nilai Al-Islam dan Kemuhammadiyahan dalam Filsafat Pendidikan Muhammadiyah Telaah Konseptual terhadap Pembentukan Karakter Mahasiswa - Annisa Maryam Nurrohmah; Masnu’atul Khoiriyah; Emilia Nurwati R; Hasnun Umar; Heri Rifhan Halili (INNOVASI : JURNAL INOVASI PENDIDIKAN, 2025)
This study aims to analyze the concept of internalization of Islamic and Muhammadiyah values in Muhammadiyah's educational philosophy and explain its implications for student character formation. This study uses a qualitative approach with a library research method, which is sourced from scientific literature, reference books, and official Muhammadiyah normative documents relevant to the research theme. The data analysis technique is carried out through content analysis by systematically examining the concepts of values, internalization, and character formation from the perspective of Muhammadiyah's educational philosophy. The results of the study indicate that Islamic and Muhammadiyah values are the philosophical foundation of Muhammadiyah education that includes theological, ethical, and social dimensions. The process of internalization of values is understood as a systemic and sustainable pedagogical mechanism, involving the integration of learning, role models, and value-based academic culture. This internalization has direct implications for the formation of integrative student character, which reflects faith, intellectuality, and social responsibility. Thus, Muhammadiyah education is directed not only at academic achievement, but also at the formation of student character with an Islamic and progressive personality in accordance with the ideals of Muhammadiyah's educational philosophy.